A Sequence Bounded Above by the Lucas Numbers - Ali Aydoğdu; Engin Özkan; Aykut Göçer (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this work, we consider the sequence whosenthterm isthe number of h-vectors of length n. The set of integer vectors E(n)isintroduced. For, n>=2,the cardinality ofE(n)is the nthLucasnumber Lnisshowed. The relation between the set of h-vectorsL(n)and theset of integer vectorsE(n)is given.